Implementation of The Right to Initiate The Formation of Regional Regulations - Tumbel, Goinpeace Handerson; Mamonto, Fitri; Supit, Brain Fransisco; Buli, Buli (Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to analyze the implementation of the right of initiative by the Regional People's Representative Council (DPRD) of Mamasa Regency and the factors influencing it in proposing regional regulations. Using a qualitative method, the study examines issues related to the legislative function during the 2014–2019 period. It highlights the unique challenges faced by Mamasa Regency, including procedural inefficiencies, minimal public participation, and limited legislative capacity. The findings reveal that during the 2014–2019 period, only 3 out of 59 regional regulations originated from the initiative of the DPRD. This is attributed to the lack of understanding among DPRD members regarding legislative procedures, budget constraints, and the limited legal education background of its members. Public participation is also restricted due to limited access to information regarding legislative session schedules. Additionally, internal coordination within the DPRD and the commitment of its members to fulfilling their legislative functions remain suboptimal, indicating a reliance on executive-proposed regulations. These findings underscore the need to enhance legislative capacity and public engagement to promote participatory and effective regional regulations.